Implementación de una plataforma tecnológica para la revista multidisciplinaria Dateh de la Universidad Técnica de Cotopaxi Extensión La Maná. - Lobato Mera, Luis Jesus (2023)
This research work aims to implement a technological platform for the editorial team of the DATEH journal of the Technical University of Cotopaxi- La Maná Extension to publish academic articles at national and international level where research results are sought not only from the Technical University of Cotopaxi but also from various research teaching centers in different parts of the world. In the first part of the project the researchers ensure the necessary foundations to support the university journal where one of the most important elements of this stage is the server, search, installation and configuration of the operating system and software by the WEB service currently available, likewise the second phase of the project management of the technology platform is to incorporate modules to support the journal information such as authors, articles, reviewers and more, while in the third phase the corresponding software engineering tests will be carried out to guarantee the quality of the system which will be available to the public on the Internet. Finally, the most important one is to incorporate the characteristics and at the same time modules that constitute the standard in its version 2. 0 of the academic information system of the Latindex profile, which through the bibliographic information research it was possible to know the different computer tools, programming languages, database managers and the methodology to be used for the development of this project. Later for the development of the platform a hosting and domain were acquired, for the web content hosting of the journal. MySQL was selected as the database manager, then, in general terms, the programming that OJS recommends was executed and subsequently with the programming languages HTML, HTML5 and PHP the codes, text, documents, visits, menu, etc. were embedded.